Ethics of Da'wah Communication Through Social Media During the COVID-19 Pandemic in Indonesia - Rosidi Rosidi; Mubasit Mubasit; Abdul Qodir Zaelani (AL-TAHRIR, 2022)
In normal situations, da’wah can be done face-to-face through ta’lim or Friday prayers, where the da’i and audience (mad’u) meet in a forum. However, such da’wah cannot be carried out in the Covid-19 pandemic situation, which has been running for almost two years. Instead, the preachers use social media such as Youtube, Instagram, WhatsApp, Facebook, and others to greet and provide enlightenment in the community. The problem is often found in social media content used by preachers with unethical language, sarcasm and lack of wisdom, especially those related to government prohibitions to reduce the risk of spreading the virus in houses of worship. Such as the prohibition of holding Friday prayers, Eid al-Fitr, Eid al-Adha, the prohibition of homecoming, holding ta’lim, and the commemoration of religious holidays, especially in the red zone category for the spread of Covid-19. This study examines the language content of da’wah communication on social media during the Covid-19 pandemic. Primary data sources are obtained from YouTube, Instagram, WhatsApp, and Facebook during the Covid-19 season. Secondary data is obtained from books, e-books, and relevant journals. This research is descriptive qualitative, with deductive and inductive thinking techniques. The research findings show that some preachers conveyed da’wah messages on social media with unethical, rude, and inappropriate languages to convey messages of a great and holy religion.